Fish tyrosinase enzyme involved in melanin biosynthesis: Insights from physicochemical characterization, homology modeling, and virtual screening studies. Issue 5 (3rd October 2022) - Kumari, Riya; Jahageerdar, Shrinivas; Panche, Archana N; Kumar, Sanath
Abstract: In the vertebrates, including fish, the tyrosinase enzyme plays an essential role in coloration. Modulation of tyrosinase activity is expected to alter the body pigmentation in fish and other vertebrate species. In the present study, physicochemical, functional, and structural properties of tyrosinase of three fish species viz ., goldfish, Japanese medaka, and common carp were determined. The homology model was developed using the Chimera1.1.2, Swiss model, and Phyre2, and the best model was selected upon evaluation. Further, a virtual screening method was applied to identify the putative modulators using the PyRx- Virtual screening tool. The estimated physicochemical and functional properties of tyrosinase from the three species suggested that they all are hydrophobic, acidic, thermostable, with a high extinction coefficient (Cys, Trp, and Tyr) and have transmembrane-segment. Based on virtual screening against 13, 000 compounds from the zinc database, five compounds were determined as potent modulators of fish tyrosinase with a binding energy of −7.0 to −8.8 Kcal/mol. Of these, Pilosine (ZINC13469966) was found to be the best putative modulator with low binding energy and properties of standardized drugs. This study showed that the tyrosinase function could be modulated to alter the pigment formation in fish species by using small compound.